Réponses

2014-05-26T19:57:17+02:00
Soit la fonction f: x --> 2x+7 Completer: 
a) f(-3) =.... 

f(x) = 2x + 7 ==> f(-3) = 2*(-3) + 7
                  ==> f(-3) = -6 + 7
                  ==> f(-3) = 1

f(-3) = 1

b) Si f(x)= 17 alors x= .... 

f(x) = 17 ==> 2x + 7 = 17
             ==> 2x = 17 - 7
             ==> 2x = 10
             ==> x = 10/2
             ==> x = 5

Si f(x)= 17 alors x= 5

c) L'image de -3 par f est ....

L'image de -3 par f est f(-3).
Or f(-3) = 1 (voir point a))

L'image de -3 par f est 1

d) L'antécédent par f de 27 est .....

Résoudre f(x) = 27

f(x) = 27 ==> 2x + 7 = 27
             ==> 2x = 27 - 7
             ==> 2x = 20
             ==> x = 20/2
             ==> x = 10